Note on Lilien and Modified Lilien index - Muhammad Rashid Ansari; Chiara Mussida; Francesco Pastore (Institute for the Study of Labor (IZA), 2013)
This note is a companion to the Lilien (lilien) and Modified Lilien (mlilien) commands for computing the relative indices in STATA. The note illustrates the main features of the commands with an application to the structural determinants of regional unemployment.
Keywords: C46; C87; J63; L16; R23; 330; econometric software; Stata commands; Lilien and Modified Lilien index; structural change; regional unemployment